Dutch East Indies, Its People, and Japan at The 1903 Osaka Exhibition - Bryna Rizkinta; Khairana Zata Nugroho; Ahmad Fauzan Baihaqi; Fauzan Syahru Ramadhan (PURBAWIDYA, 2026)
This article examines the participation of the Dutch East Indies in the 1903 Osaka Industrial Exhibition and analyzes how the exhibition functioned as a site of negotiation between colonial interests, imperial ambition, and representational politics in early twentieth-century Asia. The study analyzes the motivations behind the Indies' participation and the representation of “Indonesianness” amid colonial concern over Japan's rise. Using historical methods, namely heuristics, criticism, interpretation, and historiography, the research finds that the motivation to participate in the exhibition was not only economic but also symbolic and diplomatic, as a Western power with a long history of friendship with Japan. At the same time, the exhibition, especially the Human Pavilion, revealed how Japan articulated its modern identity by adopting and modifying international exhibition practices previously developed in Europe. Through the Human Pavilion, Japan positioned itself differently from other Asian nations, including Java and Malay. This article argues that the Osaka Exhibition represented an early expression of a hierarchical worldview and colonial imagination that was in line with patterns later seen in Japanese imperial ideology, while also revealing the Dutch's ambiguous perception of Japan as both a modern partner and a potential threat to Western colonial domination in Asia.